[Memo from Samuel D. Chilchote, Jr. (Pres. Tobacco Institute) to Executive Committee regarding testimonies in excise tax herings] - SAMUEL D. CHILCOTE JR. (Tufts Archival Research Center, 2007)
Memo from Samuel D. Chilchote, Jr. (Pres. Tobacco Institute) to Executive Committee, April 8, 1986. Requests chief corporate executive officers to testify in April 21 hearings on excise taxes. Lists other individuals/institutions expected to request time to testify. Asks for suggestions for other witnesses.